The empire's ruin - Staveley, Brian (Staveley, Brian. Ashes of the unhewn throne, 2021)
"Brian Staveley, author of The Emperor's Blades, gives readers the first book in a new epic fantasy trilogy based in the world of his popular series the Chronicle of the Unhewn Throne, The Empire's Ruin. The Annurian Empire is disintegrating. The advantages it used for millennia have fallen to ruin. The ranks of the Kettral have been decimated from within, and the kenta gates, granting instantaneous travel across the vast lands of the empire, can no longer be used. In order to save the empire, one of the surviving Kettral must voyage beyond the edge of the known world through a land that warps and poisons all living things to find the nesting ground of the giant war hawks. Meanwhile, a monk turned con-artist may hold the secret to the kenta gates. But time is running out. Deep within the southern reaches of the empire and ancient god-like race has begun to stir. What they discover will change them and the Annurian Empire forever. If they can survive"--